Analisis Kualitas Pelayanan Perizinan Berusaha Berbasis Risiko (Online Single Submission Risk Based Approach) Pada Mal Pelayanan Publik (MPP) “Grha Tiyasa” Kota Bogor - Kristiani, Marshelia; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2025)
Public service serves as a concrete benchmark for the government's performance standards. The government’s performance can be easily assessed by the public based on the quality of the services they receive. Online Single Submission (OSS) is an innovation introduced by the government to address issues in business licensing services. The government launched the risk-based business licensing service (OSS-RBA) as an improvement over previous versions of OSS (OSS version 1.0 and 1.1), which were not functioning optimally. Bogor City is one of the cities implementing OSS-RBA services through the PMPTSP Office at the “Grha Tiyasa” Public Service Mall. However, in practice, there are still several issues related to the OSS-RBA service. This study aims to analyze the quality of business licensing services (OSS-RBA) and identify the factors that drive and hinder its implementation. The research method used is qualitative descriptive, with data obtained from interviews, observations, and documentation. Informants were selected using purposive and accidental sampling techniques. The service quality measurement in this study employs the five dimensions of Zeithaml, Parassuraman, and Berry's theory: tangible, reliability, responsiveness, assurance, and empathy, along with a combination of expert theories from Moenir and Wolkins to analyze the driving and inhibiting factors, which include organizational factors, ability/skill factors, leadership factors, and recognition/reward factors. The research findings show that the quality of OSS-RBA services at the “Grha Tiyasa” Public Service Mall in Bogor City has not yet reached an optimal level. This is evident from the shortcomings found in the tangible and reliability dimensions. The driving factors in this study include organizational aspects, leadership, and the recognition or reward provided. Meanwhile, the inhibiting factors include limited abilities or skills, as reflected in the suboptimal performance of verifiers, which delays the service completion process. Additionally, the lack of specific OSS-RBA training for customer service staff due to budget constraints also contributes to the challenges.